Enhancement of silicon solar cells by downshifting with Eu and Tb coordination complexes. (27th May 2016) - Fix, T.; Nonat, A.; Imbert, D.; Di Pietro, S.; Mazzanti, M.; Slaoui, A.; Charbonnière, L. J.
Abstract: Luminescent lanthanide‐doped oxides, nanoparticles, nanocrystals, and coordination complexes are major tools in the fields of optical and laser materials, telecommunications, medical imaging, and fluoroimmunoassays. In particular, coordination complexes are efficient energy converters with high photostability, large ligand‐induced Stokes shifts, and tunable excitation and emission spectra. However, their application as light downshifting materials for solar cells has not yet been widely explored. This third generation solar cell concept enables to increase the efficiency of standard solar cells—such as Si or copper indium gallium (di)selenide (CIGS)—that have low performance for ultraviolet photons. The incorporation of such a converter in solar module encapsulants can provide a cheap and effective way to integrate photon conversion. Here, encapsulants functionalised by photon downshifting coordination complexes have been spin‐coated on silicon solar cells. For all the coordination complexes, an increase of the spectral response of the solar cells is observed in the ultraviolet region. In the best case, a relative increase of 8% of the conversion efficiency of the solar cell is observed. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : In this work, we implement different coordination complexes into a polymer encapsulant placed on silicon solar cells. Thanks to the downshifting properties of the complexes, we observe in the best case a relative increase of 8% of the solar cell efficiency. Such a high increase in efficiencies has never been observed before and is a stepping stone for future integration of functionalized encapsulants into commercial solar modules.